3D shape reconstruction of normal and cancerous red blood cells using digital holographic tomography: Combination of angular spectrum method and multiplicative technique. (25th July 2022) - Ibrahim, Dahi Ghareab Abdelsalam
Abstract: Since the red blood cell shape affects the oxygen transport, so a robust method to reconstruct the 3D shape of an RBC from different projections is presented. A robust one‐piece polarizing holographic microscope setup is used to record inline holograms of normal and cancerous red blood cells (RBCs) with high stability. The inline holograms are corrected by flat fielding and windowed Fourier filtering methods to mitigate the zero‐order and the defocused twin image due to the inline recording configuration to the least measure. The corrected inline holograms are then reconstructed by the angular spectrum method to extract the 2D wrapping phase‐contrast images. The 2D wrapping phase‐contrast images are then unwrapped using the graph cuts algorithm to extract the continuous 2D phase‐contrast images. The continuous 2D phase‐contrast images are reconstructed at different projections by the multiplicative technique to extract the 3D shape of the normal and the cancerous RBCs. Experimental results show that any deformation in the shape of the normal and the cancerous RBCs can be seen clearly at any rotational angle in 3D. This method, which is based on the degree of deformation from the best fitting, can be used as an alternative method of counting method for discrimination between normal and cancerous cells and hence diagnoses the disease easily.